The impact of improper waste disposal on human health and the environment: a case of Umgungundlovu District in KwaZulu Natal Province, South Africa - Raphela, Tlou; Manqele, Nelisiwe; Erasmus, Mariana (Frontiers in Sustainability, 2024)
Introduction Waste generation has increased drastically around the world in recent decades, with less than 20% of waste recycled each year, and one-third of all food produced wasted. With Sustainable Development Goal 12 advocating for changing how we consume, produce, and dispose of items, the cruciality of driving a more sustainable future lies in how we dispose of our waste. Methodology This study assessed the impacts of improper waste disposal on human health and the environment in the KwaZulu Natal Province of South Africa. The study applied a mixed-method pragmatic research approach, using Statistical Package for Social Scientists, and applied a series of Chi-Squared tests of independence, regression, and descriptive statistics to analyse data. This study has shed light on the complex dynamics surrounding the respondents’ awareness and perception of risks associated with improper waste disposal. Results While a fair level of knowledge exists concerning the general risks, there are notable gaps in understanding specific aspects of human health risks related to improper waste disposal. Furthermore, the study findings highlight a critical disparity in awareness regarding specific human health risks associated with improper waste disposal. Discussion This study has shed light on the complex dynamics surrounding the respondents’ awareness and perception of risks associated with improper waste disposal. This underscores the importance of enhancing public education and outreach programs to ensure a comprehensive understanding of the potential dangers to human health. The study municipality should explore sustainable waste management practices to mitigate the economic burden posed by increased waste generation.